Tuberculosis — United States, 2018. Issue 5 (24th April 2019) - Talwar, Amish; Tsang, Clarisse A.; Price, Sandy F.; Pratt, Robert H.; Walker, William L.; Schmit, Kristine M.; Langer, Adam J.
Abstract : This report reviews the current status of tuberculosis in the United States, noting the declining incidence and describing the populations with the greatest prevalence.